ANALISIS PERBANDINGAN KINERJA SISTEM PENDINGIN PV DENGAN CAIRAN AQUADES, AIR SUMUR, DAN TANPA PENDINGIN DENGAN MONITORING IOT - Wardana, Dimas Pramudya; Ahmad, Rizki Nurilyas (JURSIMA, 2024)
Solar Power Plants are an environmentally friendly energy source that utilizes sunlight energy which is converted into electricity. However, solar panels must maintain their performance. One of the impacts is that solar panels cannot work optimally if the temperature of the solar panels exceeds the safe temperature. This research examines the factors that cause the performance of solar panels to not work optimally, when the surface temperature of the solar panels is too hot and exceeds the safe temperature limit, then tools are needed to help the solar panels so that the working temperature is not too high. The technology used to control the temperature of solar panels is by utilizing IoT by maximizing the DS18B20 sensor and voltage sensor, to read the surface temperature of the panel, which will then wet the surface of the solar panel with distilled water and well water automatically if the surface temperature of the panel exceeds the safe temperature on the solar panel. And later you can monitor the temperature of the panel with a smartphone and also observe whether distilled water and well water can reduce the temperature on the surface of the panel. When collecting data, it can be compared to when without using cooling, the temperature on the panel is above 33 degrees. Meanwhile, when using a cooler the temperature obtained decreases. The well water cooler produces a temperature of 32 degrees, while the distilled water cooler produces a temperature of 30.5 degrees. It can be concluded that distilled water can reduce the temperature of the panel, so it can make the panel work optimally. So, in order to maximize the performance of the panels to utilize solar power, in this research, distilled water is very good for lowering the temperature on the surface of the panels.